Evaluasi Implementasi Program Penilaian Pembelajaran Computer Based Test (CBT) dalam Meningkatkan Mutu Sekolah di SMK Sejahtera Jakarta - Hery Muljono; Dwi Priyono; Ismah Az Zahroh (EduInovasi: Journal of Basic Educational Studies, 2024)
Computer Based Test (CBT) learning assessment at Sejahtera Vocational School has been carried out since 2016 until now. The aim of this research is to determine the results of the evaluation of the implementation of the Computer Based Test (CBT) learning assessment program in improving school quality at SMK Sejahtera Jakarta using the CIPP (Context, Input, Process, Product) model. This research uses a qualitative method with a descriptive evaluative approach. The research was carried out at Sejahtera Vocational School, North Jakarta. The subjects and data sources in this research are the Principal, Deputy Principal, IT Technician, Laboratory Assistant, Teachers and Students. The data collection techniques used were observation, interviews and documentation. The data analysis technique uses the Miles and Huberman model which analyzes data before and during the field through data reduction, data presentation and drawing conclusions. The research results show: 1) Evaluation of the context of CBT implementation indicates that there is a strong legal basis and objectives that are in line with the needs of students and schools. 2) Evaluation of inputs shows that planning, schedules, mechanisms, facilities, infrastructure, human resources and financing have gone well, although improvements to facilities and infrastructure are needed, as well as budget clarity. 3) Process evaluation shows that program implementation has gone according to plan, although there are several technical obstacles that can be overcome. 4) Product evaluation shows the success of the program with suitability between targets and results, as well as ongoing evaluation. This CBT program makes it easier for teachers and students to carry out work and corrections, so it should be continued and implemented in other places to improve the quality of education.